2001
DOI: 10.1088/0953-4075/34/9/104
|View full text |Cite
|
Sign up to set email alerts
|

Triply differential single ionization cross sections in coplanar and non-coplanar geometry for fast heavy ion-atom collisions

Abstract: We have performed a kinematically complete experiment and calculations on single ionization in 100 MeV/amu C6+ + He collisions. For electrons ejected into the scattering plane (defined by the initial and final projectile momentum vectors) our first- and higher-order calculations are in good agreement with the data. In the plane perpendicular to the scattering plane and containing the initial projectile axis a strong forward-backward asymmetry is observed. In this plane both the first-order and the higher-order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 19 publications
(18 reference statements)
6
57
0
Order By: Relevance
“…In Schulz et al (2001), it was found that the shape of the 3C-169 results was in good agreement with the shape of the experimental data for all three momentum transfers displayed in fig. 3.…”
Section: Scattering Planesupporting
confidence: 80%
“…In Schulz et al (2001), it was found that the shape of the 3C-169 results was in good agreement with the shape of the experimental data for all three momentum transfers displayed in fig. 3.…”
Section: Scattering Planesupporting
confidence: 80%
“…The first experimental FDCS were reported only about a few years ago [2,7,8], where the momenta of the ejected electron and the recoil ion were measured and the scattered projectile momentum was deduced from the conservation laws. Similar to electron impact, the data at small for electrons ejected into the scattering plane (defined by the initial and final projectile momenta) were very well reproduced by a calculation based on the continuum distorted wave approach [9].…”
mentioning
confidence: 99%
“…This, in turn, means that two momentum vectors must be measured directly; the third one is then readily given by momentum conservation. So far, FDCS were obtained either by measuring the ejected electron and projectile momenta (electron impact) or the ejected electron and recoil-ion momenta directly [2,7,8,12,13]. In our approach, the fully momentum-analyzed projectiles and recoil ions are measured in coincidence.…”
mentioning
confidence: 99%
“…In figure 1 we present results for 100 Mev amu −1 C 6+ (Schulz et al 2001) single ionization of Helium calculated in prior CDW-EIS, for different values of electron emission energy (E e ) and momentum transfer (q = K i − K f ). Calculations are in very good agreement with available experimental results.…”
Section: Resultsmentioning
confidence: 99%